Addressing English language needs of Economic Development students in Indonesian context - Dewi, Mercya Christ Sita; Indriani, Lilia (Universitas Islam Negeri Banda Aceh, 2021)
The heart of the study is English for Economics purposes as a branch of English for Specific Purposes (ESP). This study is dedicated to addressing the immediate needs of economics students in English language courses. By employing an explanatory survey method, researchers distributed a self-administrated survey and interviewed five first-year students majoring in Economic Development in one of the state universities in Indonesia. In this study, the researchers attempted to analyze Economic Development students’ target situation, present situation, and learning situation in English courses to prepare them to face global competition. The results revealed that most students admitted that English is essential for their future careers. Thus, they expected English courses should include materials related to their discipline and emphasize more authentic activities. Following the discussion, this need analysis can be a consideration in designing English learning materials for economics students.